Form and Function Predict Acoustic Transmission Properties of the Songs of Male and Female Canyon Wrens - Benedict, Lauryn; Hardt, Braelei; Dargis, Lorraine (Frontiers in Ecology and Evolution, 2021)
To function effectively, animal signals must transmit through the environment to receivers, and signal transmission properties depend on signal form. Here we investigated how the transmission of multiple parts of a well-studied signal, bird song, varies between males and females of one species. We hypothesized that male and female songs would have different transmission properties, reflecting known differences in song form and function. We further hypothesized that two parts of male song used differentially in broadcast singing and aggressive contests would transmit differently. Analyses included male and female songs from 20 pairs of canyon wrens (Catherpes mexicanus) played and re-recorded in species-typical habitat. We found that male song cascades used in broadcast singing propagated farther than female songs, with higher signal-to-noise ratios at distance. In contrast, we demonstrated relatively restricted propagation of the two vocalization types typically used in short-distance aggressive signaling, female songs and male ‘cheet’ notes. Of the three tested signals, male ‘cheet’ notes had the shortest modeled propagation distances. Male and female signals blurred similarly, with variable patterns of excess attenuation. Both male song parts showed more consistent transmission across the duration of the signal than did female songs. Song transmission, thus, varied by sex and reflected signal form and use context. Results support the idea that males and females of the same species can show distinctly different signal evolution trajectories. Sexual and social selection pressures can shape sex-specific signal transmission, even when males and females are communicating in shared physical environments.